Reconciling conservation and development requires enhanced integration and broader aims: A cross- continental assessment of landscape approaches - Estrada Carmona, Natalia; Carmenta, Rachel; Reed, James; Betemariam, Ermias; Declerck, Fabrice; Falk, Thomas; Hart, Abigail K; Jones, Sarah K; Kleinschroth, Fritz; McCartney, Matthew P.; Meinzen-Dick, Ruth S.; Milder, Jeff; et al. (Elsevier, 2024)
Expectations for agricultural landscapes in subtropical and tropical regions are high, aiming for conservation and development amid climate change, unfair trade, poverty, and environmental degradation. Landscape approaches (LAs) are gaining momentum as means to reconcile expectations, although they face multiple challenges, including unclear distinctions among LAs and stakeholder involvement. We studied 380 LAs from three continents via questionnaires with landscape managers (2012–2015 and 2021) and identiﬁed three LA types through cluster analysis: an ‘‘integrated’’ type with longer-term, multisectoral goals involving various stakeholders early in the design and two shorter-term types focused on sectoral priorities of preservation or production. Better-performing LAs are associated with longevity, inclusivity, and diversiﬁed investments across goals, notably those enabling social justice. International stakeholder analysis shows broad support for LAs but identiﬁes gaps between support and LAs’ needs. The growing interest in LAs is promising. Yet, underpinning effective and lasting LAs that reconcile multiple expectations requires better support.